Spatial epidemiology methods and applications - Elliott, P. (Paul) (Oxford : Oxford University Press, 2001)
These contributions from an international group of practitioners provide a comprehensive reference on methods and applications in the emerging field of spatial epidemiology.
Originally published: 2000.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Medical geography; Epidemiology